On increasing powder carbon steels properties using activating additives - Dyachkova, Larisa (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the possibility of increasing powder carbon steels properties by activation of carbon diffusion into the iron base during sintering process due to the introduction of the thermally split graphite (TSG), macromolecular compounds (MC) and sodium bicarbonate was investigated.
Keywords: powder carbon steels; activating additives; structure; mechanical properties